2013
DOI: 10.2478/amma-2013-0021
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Stem Cell Transplantation in Patients with Acute Myeloid Leukemia: a Single-Centre Experience

Abstract: Introduction: Autologous haemopoietic stem cell transplantation (SCT) is an important treatment modality for patients with acute myeloid leukemia with low and intermediate risk disease. It has served advantages over allogenic transplantation, because it does not need a matched donor, there is no graft versus host disease, there are less complications and a faster immune reconstitution than in the allo-setting. The disadvantage is the lack of the graft versus leukaemia effect. Materials and methods: In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…Autologous HSCT is an effective therapeutic modality in AML with the possibility of longterm survival, particularly in patients with standard-risk AML [168,169]. Several historical randomized trials have reported significantly lower relapse rates after autologous HSCT than after conventional chemotherapy [170,171].…”
Section: Autologous Hsctmentioning
confidence: 99%
See 2 more Smart Citations
“…Autologous HSCT is an effective therapeutic modality in AML with the possibility of longterm survival, particularly in patients with standard-risk AML [168,169]. Several historical randomized trials have reported significantly lower relapse rates after autologous HSCT than after conventional chemotherapy [170,171].…”
Section: Autologous Hsctmentioning
confidence: 99%
“…(1) faster hematological engraftment reflected by the recovery of blood indices, (2) the possibility of applying this form of transplant in older patients, (3) lower incidences of transplant-related complications, (4) faster immune reconstitution, and (5) absence of GVHD [169]. However, autologous HSCT has few disadvantages including: lack of GVL effect, insufficient number of peripheral stem cells at mobilization, and higher incidence of relapse [169].…”
Section: Autologous Hsctmentioning
confidence: 99%
See 1 more Smart Citation